Analysis of Defence Line Weaving for Safety Guidance Strips and Land Aircraft Safety and Communication - Dodik Widarbowo; Fajar Gumelar; Maltus Jackline Kapistrano; Wahyu Wibisono; Antoni Arif Priadi (Politeknik Siber Cerdika Internasional, 2026)
Background: Wing-in-Ground-effect (WIG) craft generate lift by operating at the air–water interface, enabling a unique mode of very high-speed maritime transport that is particularly suited to the highly complex nature of coastal and archipelagic regions. However, their distinctive operating characteristics high speed and low altitude present significant safety issues that require advanced navigation and communication systems. Objective: This paper investigates navigation and communication systems associated with the safety of WIG craft under relevant international maritime rules (International Convention for the Safety of Life at Sea SOLAS; IMO Guidelines for Wing-in-Ground Craft (MSC.1/Circ.1592). Methods: A qualitative regulatory analysis and R&D methodology is used to analyze the alignment of international standards with WIG operational requirements, as well as to examine barriers to the implementation of domestic maritime systems. Results: In the marine context, this study identifies major navigational technologies such as GNSS, radar, AIS, and integrated bridge systems for navigational awareness and collision avoidance. The integration of GMDSS communications and satellite-based technologies is indispensable for enabling coherent coordination and emergency response operations. SOLAS provisions do not fully satisfy all WIG operational requirements, while the application of IMO guidelines may result in disparate standards across jurisdictions. Conclusion: A harmonized and risk-based navigation and communication safety framework is proposed, integrating SOLAS provisions and IMO WIG Guidelines to address identified regulatory gaps. The framework aims to promote regulatory consistency and support the safe integration of WIG craft into national and international maritime transport systems.